SOME OF PIERRE BOURDIEU'S CONTRIBUTIONS TO THE SPORTS RESEARCH (Fiep Bulletin - online, 2015)
This text is an attempt to carry out a hermetic reading of the reflexive theory formulated by Pierre Bourdieu, aiming at highlighting the main aspects which should concern sports researchers who opted to work with this author. Firstly, his concepts which have been most used in works on physical education and sports were recovered, with the aim of showing that the use of such concepts must be directly related to a practical situation. The conclusion points out the necessity of constructing a general theoretical framework that points to the sports hierarchy. Such a task is only possible if the researcher understands the working logic of this space and is able to think it related to concepts such as capital, habitus and field.
Keywords: Pierre Bourdieu; Sports Field; Society.